Pengaruh Biaya Operasional terhadap Laba Bersih Perusahaan Manufaktur Sektor Industri Makanan dan Minuman yang Terdaftar di BEI Tahun 2020-2022 - Hayati, Sri; Wirananda, Henny Andriyani (Jurnal EMT KITA, 2025)
The purpose of this study is to determine the partial and simultaneous effects of production costs, sales costs and other costs on net profit in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022. This research is a quantitative study. The research sample used a saturated sampling method with a total of 33 samples. The data analysis technique for this study used the classical assumption test method, multiple linear regression analysis, and hypothesis testing. The results of the partial test value of production costs tcount 13.608> ttable 1.699 significance 0.000 <0.05. The partial test value of sales costs tcount 1.765 <ttable 1.699 significance 0.001 <0.05 and the partial test value of other costs tcount -20.144 <ttable 1.699 significance 0.000 <0.05. Simultaneously, the Fcount value is 235.996 > Ftable 2.92, significance 0.000 < 0.05. The conclusion of the analysis results shows that production costs and sales costs partially have a significant effect on net sales, and other cost variables have a negative effect on the company's net profit. Production costs, sales costs and other costs simultaneously have a significant effect on net sales.